2022
DOI: 10.3390/en15072551
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Fueled Binary Energy System with Low-Boiling Working Fluid for Enhanced Power Generation

Abstract: This article discusses methods of enhanced power generation using a binary power system with low-boiling fluid as an intermediate energy carrier. The binary power system consists of micro-gas and steam power units and is intended for remote standalone power supply. Trifluotrichloroethane was considered as the working agent of the binary cycle. The developed system was modeled by two parts in MATLAB Simulink and Aspen HYSYS. The model in Aspen HYSYS calculates the energy and material balance of the binary energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Issues of improving power quality are addressed in many scientific articles by researchers from almost all countries of the world [1][2][3]. One of the main tasks within this area is to reduce the influence of harmonics on the operation of electrical equipment during the generation, transmission, distribution and consumption of electrical energy [4][5][6]. The relevance of this problem is emphasized by the significant increase in cases being considered in arbitration disputes between suppliers and consumers of electrical energy [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Issues of improving power quality are addressed in many scientific articles by researchers from almost all countries of the world [1][2][3]. One of the main tasks within this area is to reduce the influence of harmonics on the operation of electrical equipment during the generation, transmission, distribution and consumption of electrical energy [4][5][6]. The relevance of this problem is emphasized by the significant increase in cases being considered in arbitration disputes between suppliers and consumers of electrical energy [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analysis of the problems of the energy market [1][2][3] and the current green energy agenda [4][5][6], it may be concluded that the issues of waste energy source recovery are among the most pressing. For liquefied natural gas (LNG), one of the possible ways to solve this issue is the recovery and recycling of its boil-off gas, which nowadays is discharged from the LNG tanks using ejectors [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the dynamic component of WOB for drilling with cone bits and extending their motor resource to the level of PDC bits operation time will be presented in the next scientific works of the Mining University [57][58][59].…”
mentioning
confidence: 99%